AMETEK to Acquire Solartron Group (Advanced Battery Technology, 2005)
AMETEK Inc. of Paoli, Pennsylvania, has agreed to acquire the Solartron Group from Roxboro Group PLC for approximately$75 million. Solartron, with annual sales of about $50 million, is a leading supplier of analytical instrumentation for the process, laboratory and other industrial markets. This acquisition, expected to be completed by the end of the third quarter, is subject to normal closing conditions including approval by Roxboro's shareholders. Solartron is composed of three businesses: Solartron Analytical, Solartron Metrology and Solartron ISA. Solartron Analytical produces high-precision analytic measurement instrumentation and software for the characterization of materials. Its products are used for electrochemistry, corrosion analysis and advanced materials analysis and are sold to research, metals, and other industrial markets including the fuel cell industry. Together with its Princeton Applied Research business unit, AMETEK will be the market leader for these instruments.